(untitled) - Jackson, Daniel M. (New York, 2003)
Brands have become very important as sources of value and a means to build value and sustain market position. Much emphasis has been placed upon the visual representation of brands, but this book defines a new competitive arena in the creation and development of brands--sound. Sonic branding is a new, fast-growing area related to advertising and media development of the branding experience. This will be a distinctive book and the first in this important new area.
Keywords: Advertising,Music in advertising; Brand name products